Fe‐Ni‐Mo Nitride Porous Nanotubes for Full Water Splitting and Zn‐Air Batteries. Issue 36 (13th November 2018) - Zhu, Chunling; Yin, Zhuoxun; Lai, Weihong; Sun, Yue; Liu, Lina; Zhang, Xitian; Chen, Yujin; Chou, Shu‐Lei
Abstract: High‐performance catalysts are required in various energy storage and conversion systems. In this work, hierarchical Ni‐Fe‐Mo trimetal nitride nanotubes (NTs) as highly efficient, low‐cost, robustly stable, multifunctional catalysts through room‐temperature Fe incorporation and subsequent thermal treatment for full water splitting and Zn‐air batteries are fabricated. The two‐electrode electrolyzer assembled from the NTs delivers a current density of 10 mA cm −2 at 1.513 V, outperforming the precious metal IrO2 |Pt couple and state‐of‐the‐art bifunctional catalysts. Furthermore, two all‐solid‐state Zn‐air batteries with the hierarchical NT air cathode in series can power 55 red light‐emitting diodes with excellent operation stability, at the same time as the electrolyzer based on the hierarchical NTs. Abstract : An alkaline electrolyzer and zinc‐air battery assembled with trifunctional Ni‐Fe‐Mo nitride nanotubes exhibits excellent electrochemical properties. The electrolyzer shows remarkable activity with a current density of 10 mA cm −2 at a voltage of 1.513 V, superior to the Pt and IrO2 couple, and can be self‐powered by the Zn‐air battery with the nanotubes as air‐cathode.